PTH-002 A Single Centre Audit Comparing Colonoscopy Completion and Complication Rates in older and Younger Patients. (4th June 2013) - Harrison, L; Parish, R; Shenderey, R
Abstract : Introduction: Colonoscopy is the gold standard test for large bowel assessment. Radiological techniques are available and have a high sensitivity and specificity for diagnosing colorectal cancer. 1 As part of the Joint Advisory Committee (JAG) for endoscopy accreditation, units should achieve a caecal intubation rate of > 90%. We audited our unit's performance. Methods: We audited colonoscopies carried out in 2011 at a District General Hospital. Endoscopy reports of 75 patients aged 80 and over and 75 patients under 75 years old were analysed. Results: 1635 colonoscopies were carried out by the unit in 2011. The pick-up rate for cancer was at least 3.5% and for polyps was 23%. Completion of colonoscopy in under 75 year olds was 97%. Completion in over 80 year olds was 79%. The unit's overall completion rate in 2011 was 90% (24% terminal ileum, 65% caecum, 1% anastomosis). Colonoscopy was better tolerated in the younger group with discomfort suffered in 7% of patients compared to 11% of elderly patients (see table 1 ). The overall pick-up rate for cancer in both groups was 3%. Conclusion: The completion rate in the elderly (79%) was below the standard as set by JAG (> 90%). This was due to more discomfort experienced by the elderly group and more complications. There were six new colorectal cancer diagnoses in the elderly. These cancers could have been diagnosed by radiographic techniques such as CT colonography or CT with faecal tagging. The 2011 NICE guidance on the management of colorectal cancer2 states that CT colonography can be used as a safe and effective alternative to colonoscopy. This audit demonstrates that patient selection for colonoscopy is very important. CT colonography should be considered for the first line investigation in the elderly to reduce unnecessary complications and low overall colonoscopic completion rates. Disclosure of Interest: None Declared. References: Pickhardt PJ, Hassan C, Halligan S, Marmo R. Colorectal cancer: CT colonography and colonoscopy for detection–systematic review and meta-analysis. Radiology 2011; 259(2):393–405. National Institute of Health and Clinical Excellence. Colonoscopic surveillance for prevention of colorectal cancer in people with ulcerative colitis, Crohn's disease or adenomas. London: NICE 2011. http://www.nice.org.uk/nicemedia/live/13415/53641/53641.pdf [Accessed 5/1/13]